PELANGGARAN ETIKA PARIWARA INDONESIA DALAM IKLAN BLIBLI DAN GOJEK - Ramadhani, Reihana Bornov; Norfauzi, Rikza; Rama, Taufik Adi; Junaedi, Fajar (Universitas Muhammadiyah Jakarta, 2024)
This research aims to analyze the ethical violations in advertising that occur in Blibli and Gojek YouTube ads. This research is using a qualitative descriptive method to answer the problem formulation, namely how violations of the Indonesian Advertising Ethics can occur in Blibli and Gojek ads. Qualitative research is a form of research to gain a deeper understanding of the problem phenomena. The findings of this research indicate that there are violations in Blibli and Gojek ads through the use of superlative words, particularly in statements such as